The story of his life as he tells it : - Pambrun, Andrew Dominique, 1822-1895
Born in Little Rock, Arkansas, grew up in Canada and the Pacific Northwest. Father worked for the Hudson's Bay Company. Mr. Pambrun worked for the Hudson's Bay Company in Walla Walla before attempting gold mining in California. Returned to Oregon in the 1850's during the Indian Wars. Died in Walla Walla in 1895.